Developing, delivering and evaluating stroke specific vocational rehabilitation: a feasibility randomised controlled trial - Grant, Mary (2016)
Background Approximately 152,000 people have a stroke in the UK every year, a quarter are working age and only 40% return to work. Vocational rehabilitation (VR) provision is patchy in the UK and has not been evaluated for the stroke population. Aim This study aimed to develop, deliver and evaluate stroke specific VR in a feasibility randomised controlled trial (RCT) in one English county. Method A qualitative interview study with key stakeholders sought to explore barriers to and unmet needs for support for stroke survivors intending to return to work. The findings, two case studies and an expert panel informed the development of a stroke specific VR intervention. Its potential effectiveness in influencing occupational status at 12 months post baseline was measured in a feasibility RCT. Intervention content was analysed and the stroke survivors and employers who received it were interviewed about its usefulness and acceptability. Results 18 key stakeholders identified barriers to VR in existing service design and delivery. Stakeholders identified the need for individualised, responsive, timely and flexible intervention including support for family members and employers. 46 people, with mainly minor and moderate strokes, were recruited to the feasibility trial and 23 randomised to stroke specific VR. Delivery and compliance with intervention was feasible. Only one participant withdrew. Follow-up was feasible at three, six and 12 months post baseline as indicated by an overall response rate of 73.9%. Twice as many participants returned to work in the intervention group. Data collection on income and benefit status was problematic due to missing data. Secondary measures included quality of life, function, mood and participation. A proforma was successfully used to record and measure intervention content, which showed that stroke specific VR is an individually tailored complex intervention involving cross sector working. 12 stroke survivors and six employers interviewed following the trial, valued this flexible, individualised intervention which positively influenced return to work experiences and outcomes. Discussion Stroke severity influenced participation and a different model may be needed for those with severe stroke and those unable to return to an existing job. Employer contact was not always possible or desired by the stroke survivor. Funding, targeting and implementing this type of intervention requires further consideration. Conclusion Early intervention can potentially influence job retention rates in people with mild and moderate stroke but a larger trial is needed to demonstrate effect.